Help for the Workers of Spain Fund : inter-departmental correspondence - Tewson, Vincent
028-0143-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From: H. V. Tewson. To: Sir Walter Citrine. Department: Secretary's. Date: 8th December, 1936. SUBJECT. HELP FOR THE WORKERS OF SPAIN FUND. The attached letter from the East Ham North Labour Party raises the question as to whether we should give further publicity to the Spanish Fund and state the amount of money which has been raised, together with information as to its disposal on the lines of Schevenels' letter. At a time when there is a general impression that nothing is being done in regard to Spain don't you think it might be well just to give the "Herald" a general statement? Yes, but let me see a draft. C 292/946/28/143